2010
DOI: 10.1016/s1734-1140(10)70366-2
|View full text |Cite
|
Sign up to set email alerts
|

1-Methyl-1,2,3,4-tetrahydroisoquinoline and established uncompetitive NMDA receptor antagonists induce tolerance to excitotoxicity

Abstract: The aim of this study was to establish the antagonistic effects of 1-methyl-1,2,3,4-tetrahydroisoquinoline (1MeTIQ) on NMDA receptors and its neuroprotective abilities on primary cultures of rat cerebellar granule cells exposed for 30 min to 250 or 100 μM glutamate. Neuronal viability was tested after 24 h with propidium iodide or calcein/ethidium homodimer-1 staining. The neuroprotective potential of 100, 250 or 500 μM 1MeTIQ was compared with established uncompetitive NMDA receptor antagonists, 0.5 μM MK-801… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…More recently we confirmed these data in cultured cerebellar granule cells (CGC) [36]. In addition, our recent unpublished data demonstrate that in CGC both (+)MK-801 and memantine induce tolerance to oxygen and glucose deprivation (OGD), which is an in vitro model of brain ischemia.…”
Section: Introductionsupporting
confidence: 72%
“…More recently we confirmed these data in cultured cerebellar granule cells (CGC) [36]. In addition, our recent unpublished data demonstrate that in CGC both (+)MK-801 and memantine induce tolerance to oxygen and glucose deprivation (OGD), which is an in vitro model of brain ischemia.…”
Section: Introductionsupporting
confidence: 72%
“…Also in vivo study demonstrated the anticonvulsant activity of 1MeTIQ which elevated the threshold for electroconvulsions in mice, and enhanced the protective action of carbamazepine and valproate against maximal electroshock-induced seizures in mice (Luszczki et al 2006). What’s more, a neuroprotective effect of 1MeTIQ was shown in cultured rat cerebellar granule cells in a model of glutamate-evoked, NMDAR-mediated excitotoxicity (Antkiewicz-Michaluk et al 2006; Kuszczyk et al 2010). More specifically, 1MeTIQ in high μmolar concentrations which antagonized neuronal death also reduced 45 Ca uptake induced by glutamate, and inhibited binding of radioactive [ 3 H]MK-801 to isolated brain membranes (Antkiewicz-Michaluk et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies provide evidence that 1MeTIQ is a low affinity NMDAR antagonist. 1MeTIQ was found to inhibit binding of [ 3 H]MK-801 (dizocilpine) to isolated neuronal membranes (Kuszczyk et al 2010) and prevents glutamate-induced excitotoxicity and influx to neurons of calcium radio-labeled with the isotope 45 Ca (Antkiewicz-Michaluk et al 2006). What’s more, as was shown previously 1MeTIQ at concentrations of up to 500 μM does not decrease viability of neurons in primary culture, but exhibits neurotropic and neuroprotective properties (Antkiewicz-Michaluk et al 2006; Kotake et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We chose two protocols for memantine treatment based on previous studies that used similar treatment protocols 4,21 : pretreatment for one hour followed by one hour glutamate treatment and treatment at the same time as glutamate treatment. Because glutamate is released during the secondary phase of TBI, it is possible that patients could be protected with memantine after the initial mechanical injury has occurred but before excess glutamate begins to accumulate.…”
Section: Discussionmentioning
confidence: 99%